1982
DOI: 10.1044/jshd.4701.99
|View full text |Cite
|
Sign up to set email alerts
|

Pragmatic Analysis of the Communicative Behavior of an Autistic Child

Abstract: Differential responsiveness by social stimuli was demonstrated in the communicative performance of an 8-year-old autistic boy. The pragmatic behavior of the subject varied with different communicative settings (waiting vs. interaction conditions) as well as with different communicative partners (mother, stranger, clinician). Communicative intentions, relational communication, topic strategies and differential responding to adults to communicative and non-communicative utterances were analyzed. Results indicate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0
7

Year Published

1985
1985
2015
2015

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 66 publications
(39 citation statements)
references
References 0 publications
1
31
0
7
Order By: Relevance
“…Children, including autistic children (cf. Bernard-Opitz, 1982), are more verbal and use more advanced language with someone they know well in a familiar setting.…”
mentioning
confidence: 99%
“…Children, including autistic children (cf. Bernard-Opitz, 1982), are more verbal and use more advanced language with someone they know well in a familiar setting.…”
mentioning
confidence: 99%
“…It may suggest that the isolated communicative intent (no adequately addressed) doesn't result in functional efficiency. This brings to attention the issue of the need to take the communicative context into consideration when analyzing pragmatic abilities of individuals with ASD [5,12].…”
Section: Results and Commentsmentioning
confidence: 99%
“…Studies have shown that individuals of the autistic spectrum present communicative intent (Molini and Fernandes, 2003) and are sensitive to the communicative partner (Bernard-Optiz, 1982). This author studied the interference of different interlocutors in the communication of children with autism.…”
Section: Introductionmentioning
confidence: 99%
“…In the literature few studies (Bernard-Optiz, 1982;Fernandes, 2000a) focus on the therapistchild rapport although this dyad is always considered potentially important to the prognosis of the child of the autistic spectrum. Fernandes (2000a) studied the functional aspects of the communication of children with autism in the context of language therapy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation